Análise dos determinantes dos rendimentos no Serviço Público Estadual: o caso do executivo do Estado do Ceará - Braga, Bruno Alexandre (2012)
Using data from the State Department of Planning and Management, this study presents a profile of salaries for civil public servants of the State of ceará and proposes estimation of income to assess the Mincerian determinants of wages in eight different occupational groups according to their levels of education, experience, administrative experience, gender and physical location of the servants. It appears that contributions of schooling on cornings growth from 5% to 19 % among the occupational groups studied and, eventhough it is confirmed in some cases, the diminishing marginal contribution of the experience on the income tax was rejected. Moreover, there is a differentiated evolution of the level of income among the servants in the metropolitan region of Fortaleza in most occupational groups examined.